Sistem Informasi Jasa Laundry Berbasis Web Dengan Metode SDLC Waterfall Pada Laundry Multi - Ermanto; Riko Bilal Febriyanto (DPPM Universitas Pelita Bangsa, 2023)
The laundry service business has grown rapidly, particularly in areas around universities, increasing the demand for fast and affordable laundry services. Laundry Multi still manages transaction records manually using paper receipts, resulting in inefficient data processing and a higher risk of recording errors. This study aims to design and develop a web-based laundry service information system to improve the efficiency of transaction and report management. The system was developed using the System Development Life Cycle (SDLC) method with the Waterfall model, consisting of analysis, design, implementation, and testing stages. The system was implemented using PHP programming language with a MySQL database. The results show that the developed system facilitates transaction data management, accelerates report generation, and improves the overall quality of services at Laundry Multi.